THERMODYNAMIC AND REACTIVITY ASPECT OF β-CYCLODEXTRINE INCLUSION COMPLEXES WITH COUMARIN DERIVATIVES - José Muñoz; Germán Barriga (Journal of the Chilean Chemical Society, 2022)
In this study, the thermodynamic and reactivity characteristics of coumarin-derived ligand inclusion complexes with βCD were described, in addition to the in situ reactivity of these ligands and their changes in the complex cavity. For this purpose, computational tools such as molecular docking, second order perturbative analysis (E2PERT), ONIOM2 (DFT/PM6) methods were employed to obtain the global and local reactivity indices, and thermodynamic parameters, in addition to non-covalent interaction (NCI) analysis. As a result, it can be observed that the inclusion complexes are stable and viable given the ability to form non-covalent interactions, but their formation is not spontaneous under the modeling conditions. The global and local reactivity indices show that the ligands change their chemical reactivity inside the inclusion complex, demonstrating that the studied ligands present AOX SET activity outside the cavity, and HAT activity inside the cavity, mainly the C1 and C3 ligands.